Orientation-dependent spin-polarization and transport properties in altermagnet based resonant tunneling junctions - Kai-Yi Lyu; Yu-Xian Li (Results in Physics, 2024)
We investigate the spin-dependent spin-polarization and transport properties in altermagnet-based resonant tunneling junctions, in which the altermagnet has two symmetric orientations of spin-split Fermi surface. In the first model the Fermi surface is an ellipse with the major axes either parallel or perpendicular to the altermagnet/barrier interface, and the Fermi surface in the second one is also an ellipse but the major and the minor axes have the same angle relative to the altermagnet/barrier interface. Our findings reveal that the transport properties for spin-up and spin-down electrons are spin polarized and depend on the orientation of the altermagnet with respect to the interface. In contrast to conventional ferromagnetic and antiferromagnetic splitting mechanisms, the transmission in our study exhibits spin splitting with an alternating sign. For the first model, the total spin-polarization is zero, indicating a lack of net magnetization due to the combined effects of spin and real-space symmetries, thereby reflecting normal metal properties. Conversely, in the second model, a discernible total spin-polarization emerges, indicative of ferromagnetism. These orientation-dependent transport properties exemplify the unique features of the altermagnetism. The anisotropic altermagnetic state in momentum space can be measured by the orientation-dependent conductance in these resonant tunneling junctions.